Experimental evaluation of liver regeneration patterns and liver function following ALPPS. Issue 3 (24th October 2017) - Shi, J. H.; Hammarström, C.; Grzyb, K.; Line, P. D.
Abstract : Background: The underlying mechanism of liver regeneration after Associating Liver Partition and Portal vein ligation (PVL) for Staged hepatectomy (ALPPS) is still unclear. The aim of this study was to evaluate the relationship between future liver remnant (FLR) volume, liver regeneration characteristics and restoration of function in an experimental model of ALPPS. Methods: An ALPPS model in rats was developed with selective PVL, parenchymal transection and partial hepatectomy (step 1), followed by resection of the liver (step 2). Three different ALPPS groups with FLR sizes of 30, 20 and 10 per cent of total liver volume were compared with sham‐operated controls and animals undergoing resection of left lateral lobe and 90 per cent PVL with respect to morbidity, mortality, liver regeneration and function. Results: Three of 15 animals that had ALPPS with 10 per cent FLR (ALPPS10) died after step 1. Ascites developed in two of five rats that had ALPPS with 20 per cent FLR and in three of four animals in the ALPPS10 group after step 2. Although the relative increments in FLR size and growth rates were highest in the ALPPS groups, small FLR size was associated with a sustained increase in levels of serum aminotransferases and bilirubin, a lower albumin concentration, severe sinusoidal injury, increased expression of proliferation markers and increased activation of hepatic progenitor cells after step 2. Conclusion: There is discordance between FLR volume increase and functional restoration after the ALPPS procedure. Abstract : Associating Liver Partition and Portal vein ligation (PVL) for Staged hepatectomy (ALPPS) is a new strategy to expand the future liver remnant (FLR). ALPPS‐associated morbidity, mortality and the mechanism of liver regeneration remain unclear. To evaluate the relationship between FLR size, postoperative liver regeneration and function restoration in ALPPS, a rodent model of ALPPS was developed with selective PVL, parenchymal transection and partial hepatectomy (step 1), followed by resection of the deportalized liver (step 2). Results showed that hepatic sinusoidal injury related to FLR size could result in functional impairment and mortality after ALPPS surgery. Hepatic hypertrophy after ALPPS with a low FLR was associated with increased Hippo/YAP signalling and hepatic progenitor cell (HPC) activation. Sinusoidal injury and repopulation of HPCs are relevant for the disconcordance between FLR volume increase and functional compensation, which might provide a better understanding of ALPPS surgery. Understanding how ALPPS works